2019
DOI: 10.5152/tud.2018.98048
|View full text |Cite
|
Sign up to set email alerts
|

The effect of atorvastatin on penile intracavernosal pressure and cavernosal morphology in normocholesterolemic rats

Abstract: The present study showed that the use of atorvastatin reduced the intracavernosal pressure in 10 V stimulation, and minimally decreased testosterone levels in rats, within a short period of time. When statin treatment is considered for its protective properties on cardiovascular system or for its lipid-lowering effect. It should be kept in mind that atorvastatin may also adversely contribute to erectile dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The results indicated a signi cant association between atorvastatin and ED (40) . Mustafa Suat Bolat et al found through animal experiments that atorvastatin can reduce testosterone levels in rats and the intracavernosal pressure under 10v stimulation, suggesting that the drug may affect the rearrangement of collagen and elastic bers in the corpus cavernosum, ultimately impacting penile erection (41) . Currently, most studies indicate that atorvastatin, while lowering cholesterol levels, can also affect testosterone synthesis and libido, ultimately leading to ED (10) .…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated a signi cant association between atorvastatin and ED (40) . Mustafa Suat Bolat et al found through animal experiments that atorvastatin can reduce testosterone levels in rats and the intracavernosal pressure under 10v stimulation, suggesting that the drug may affect the rearrangement of collagen and elastic bers in the corpus cavernosum, ultimately impacting penile erection (41) . Currently, most studies indicate that atorvastatin, while lowering cholesterol levels, can also affect testosterone synthesis and libido, ultimately leading to ED (10) .…”
Section: Discussionmentioning
confidence: 99%
“…However, Akdeniz et al observed a significant reduction in the number of spermatogonia and spermatocytes in male Sprague-Dawley rats following 12 weeks of atorvastatin intervention compared to the comparison group ( Akdeniz et al, 2021 ). In their animal experiments, Bolat et al found that atorvastatin can rapidly decrease intracavernosal pressure under 10 V stimulation in rats, lower testosterone levels, and impact sexual function ( Bolat et al, 2019 ). In their study, Baspınar et al found that patients on statin therapy might observe a rise in NO levels; however, a decrease in NO levels could occur when their LDL-C levels reach 100 mg/dL.…”
Section: Discussionmentioning
confidence: 99%
“…Atorvastatin may also cause ED because of its effect on testosterone, with studies suggesting that atorvastatin may negatively affect erectile function by interfering with testosterone synthesis and metabolism and reducing testosterone levels ( Bolat et al, 2019 ). This impact could be linked to the hindrance of the cholesterol synthesis pathway, given that cholesterol serves as a vital precursor for testosterone synthesis ( Dobs et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, other investigations have found that atorvastatin has a negative effect on erectile function. Atorvastatin can lower penile intracavernosal pressure (ICP) and testosterone levels in rats, potentially leading to ED (Bolat et al, 2019). Additionally, other studies have demonstrated that atorvastatin treatment can decrease LDL-C F I G U R E 4 Meta-analysis of single-arm clinical trials (SATs) on the effect of atorvastatin on erectile dysfunction levels, which may be associated with a reduction in testosterone levels and erectile function (Baspınar et al, 2016).…”
Section: Discussionmentioning
confidence: 99%